Titania modifications with fluorine, sulphates and platinum for photochemical reduction of chromium (VI)” - Julie Joseane Murcia; Mónica Sirley Hernández-Laverde; Ivan Alexander Correa-Camargo; Hugo Alfonso Rojas-Sarmiento; José Antonio Navío; Maria del Carmen Hidalgo-López (Revista Facultad de Ingeniería Universidad de Antioquia, 2024)
In this work, Titania was modified by sulfation or fluorination and platinum on the surface to improve the Cr (VI) reduction efficiency compared to the bare TiO2 material synthesized by the sol-gel method. The synthesized materials were characterized by XRD, SBET, UV-Vis DRS, XRF, TEM, FTIR, and XPS. The modifications led to higher stability in the Anatase phase and surface area of this semiconductor. The addition of F and Pt in TiO2 led to absorption increases in the visible region of the electromagnetic spectrum. A correlation between the new physicochemical properties obtained after TiO2 modification and the photocatalytic performance of this material was observed. The best result in chromium reduction was obtained using Pt-S-TiO2 as the photocatalyst; this material showed a suitable combination of surface area, high UV-Vis absorption, high hydroxylation, and the existence of Pt nanoparticles on the surface, which favors an increased electron-hole pair half-life. Different reaction parameters were also evaluated, which demonstrated that the best photocatalytic performance was obtained under an N2 atmosphere, a light intensity of 120 W/m2, and 2 hours of total reaction time. Likewise, it was noted that an increase in reaction time from 2 to 5 hours, had a detrimental effect on reducing Cr (VI) efficiency.